A million quiet revolutions eaudiobook - Gow, Robin (Spotify Audiobooks, 2022)
Robin Gow's A Million Quiet Revolutions is a modern love story, told in verse, about two teenaged trans boys who name themselves after two Revolutionary War soldiers. A lyrical, aching young adult romance perfect for fans of The Poet X, Darius the Great is Not Okay, and Aristotle and Dante Discover the Universe. "Robin Gow's A Million Quiet Revolutions is a stunning, lyrical love story about discovering our identity (and what that means for us) and the importance of seeing ourselves reflected in history. A gorgeous debut." ―Nicole Melleby, author of Hurricane Season and In The Role of Brie Hutchens For as long as they can remember, Aaron and Oliver have only ever had each other. In a small town with few queer teenagers, let alone young trans men, they've shared milestones like coming out as trans, buying the right binders―and falling for each other. But just as their relationship has started to blossom, Aaron moves away. Feeling adrift, separated from the one person who understands them, they seek solace in digging deep into the annals of America's past. When they discover the story of two Revolutionary War soldiers who they believe to have been trans man in love, they're inspired to pay tribute to these soldiers by adopting their names―Aaron and Oliver. As they learn, they delve further into unwritten queer stories, and they discover the transformative power of reclaiming one's place in history.